Studying The Expression of Human TGFB1 Gene in Patients Carrying Breast Cancer - Dawood Salim Edan (College of Pharmacy / Mustansiriyah University, 2018)
TGFB1 gene encodes a member of the transforming growth factor beta (TGFB) family of cytokines, that play multifunctional roles in regulation the proliferation, differentiation, and other functions in different cell types. Therefore, we collected thirty samples from Yarmouk hospital in Baghdad ,Iraq. Twenty- nine from women patients carrying Breast cancer and the last one was from healthy woman. and the samples that we have taken were embedded in paraffin wax, The extracted RNA from each samples was used to check the expression of TGFB1 gene via Real time PCR. We designed primers of TGFB1 gene on encoded sequence (Exon), to make sure generation a specific PCR product of TGFB1 gene by converting mRNA to cDNA then PCR Product , The expression of each samples was fluctuated between 0.1 fold to 0.2 fold compared with the control ( the healthy sample). The highest expression showed was samples 14 with 0.2 fold , and the lowest expression showed was samples 27 with approximately 0.1 fold that is similar relatively compared with control expression . The results indicate that tumor may affects on a TGFB1 gene and can increase the gene expression, and eventually can increase the TGFB1 protein that can be used for upregulation of the cells that carried the cancer.